Intelligent response type antibacterial-nano composite protective coating and preparation method thereof
Through the synergistic action of ZnO@rGO and Ag@mSiO2/PAA, combined with the epoxy resin matrix, efficient antibacterial protection is achieved in complex environments, solving the problem of instability and insufficient adhesion of antibacterial agents in acid and alkali environments of the coating, and providing a long-term and on-demand antibacterial effect.
Patent Information
- Application Number
- CN202510501113.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-21
- Publication Date
- 2025-07-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing coatings have unstable antibacterial properties and insufficient long-term performance in complex environments. Antibacterial agents are prone to loss and resources are wasted, and they have failed to achieve on-demand release.
Zinc oxide-graphene composite (ZnO@rGO) is used to provide superhydrophobicity, mesoporous silica/polyacrylic microcapsules (Ag@mSiO2/PAA) is used to achieve pH-responsive sustained-release antibacterial, and epoxy resin matrix forms an external hydrophobic-internal strong structure, and the antibacterial agent is released on demand through dynamic pH response mechanism and gradient ultraviolet curing process.
The silver ions are efficiently released in acidic environments, with an antibacterial rate of ≥95%, and the ineffective release is reduced in alkaline environments. The coating adhesion level is ≥4B, which is erosion-resistant and reduces bacterial resistance.
Smart Images

Figure BDA0005368486010000061
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of chemical anti-corrosion materials, and particularly relates to an intelligent responsive antibacterial-nano composite protective coating and a preparation method thereof, which are applicable to the protection of coal chemical pipelines in environments containing hydrogen sulfide (H2S), microbial corrosion, and high temperature and high pressure. Background Art
[0002] During the actual operation of coal chemical pipelines, they are exposed to extremely complex environments for a long time, and the corrosion problem is particularly prominent. Specifically, the environment where the pipelines are located usually contains high concentrations of hydrogen sulfide, with a concentration up to 800 ppm, high temperature and high pressure conditions (temperature ≤ 500 °C, pressure up to 10 MPa), and highly active sulfate-reducing bacteria (SRB, activity > 10 4 CFU / mL). These factors are coupled with each other, greatly accelerating the corrosion rate of the pipelines.
[0003] A superhydrophobic corrosion-resistant antibacterial nano-coating, coating and preparation method thereof (CN 114561138 B) discloses the compounding of benzoxazine nanoparticles and epoxy resin. Although it has superhydrophobicity, the antibacterial agent is released statically (direct doping of silver ions), and it is easy to be washed away by fluid flow. After 3 months, the antibacterial rate drops by more than 50%. A graphene nano-coating and preparation method thereof (CN 119192972A) discloses improving the adhesion by modifying graphene oxide with chitosan, but does not introduce an antibacterial response mechanism, and the antibacterial rate drops below 30% when pH > 9. A preparation method of a superhydrophobic self-cleaning nano-coating (CN119081540 A) discloses sensor-triggered coating repair, but does not solve the problem of on-demand release of antibacterial agents, resulting in waste of resources and uneven local concentration. Summary of the Invention
[0004] To solve the core problems of unstable antibacterial performance and insufficient long-term effectiveness of existing coatings in complex environments, the present invention provides an intelligent responsive antibacterial-nano composite protective coating. The surface layer ZnO@rGO provides superhydrophobicity, with a contact angle ≥ 160°. The middle layer Ag@mSiO2 / PAA slowly releases antibacterial agents, and the bottom layer epoxy resin ensures adhesion, with a grade ≥ 4B. These three layers form an outer hydrophobic-inner tough structure. Another technical problem to be solved by the present invention is to provide a preparation method of an intelligent responsive antibacterial-nano composite protective coating, which realizes on-demand release of antibacterial agents, long-term protection, and high mechanical strength through a dynamic pH response mechanism, a synergistic effect of biphasic nanoparticles, and a gradient ultraviolet curing process.
[0005] To solve the above technical problems, the technical solutions adopted by the present invention are as follows:
[0006] An intelligent response antibacterial-nano composite protective coating, which consists of a surface layer, an intermediate layer and a bottom layer; the surface layer is a zinc oxide-graphene composite (ZnO@rGO), which is used to release Zn in an acidic environment 2+ to inhibit microbial metabolism; the intermediate layer is a silver-loaded mesoporous silica / polyacrylic acid microcapsule (Ag@mSiO2 / PAA), which is a pH-responsive microcapsule. In an acidic environment (pH < 7), it dissolves and releases silver ions, and in an alkaline environment (pH > 7), it self-closes to reduce ineffective release (release amount ≤ 1 μg / cm 2 ·day), and can release Ag in a long-term sustained manner + , and the antibacterial rate is ≥ 95% (for 28 days); the bottom layer is an epoxy resin matrix, which forms an outer hydrophobic-inner tough structure through ultraviolet curing.
[0007] For the intelligent response antibacterial-nano composite protective coating, the thickness of the surface layer is 50-100 μm; the thickness of the intermediate layer is 30-50 μm; the thickness of the bottom layer is 100-150 μm.
[0008] For the protective coating, reduced graphene oxide (rGO) and ZnO nanoparticles are dispersed in ethanol, ultrasonically treated for 2 hours, transferred to a high-pressure reactor, reacted at 160 °C for 8 hours, centrifuged and washed, and dried at 60 °C to obtain the ZnO@rGO composite.
[0009] For the protective coating, the mass ratio of zinc oxide nanoparticles to rGO in the zinc oxide-graphene composite is 4:1, the average particle size of ZnO nanoparticles is 20-30 nm, and the rGO sheet size is 1-2 μm.
[0010] For the protective coating, mesoporous silica is immersed in a silver nitrate solution, ultrasonically treated for 1 hour, and then calcined at 300 °C for 2 hours to obtain Ag@mSiO2; then Ag@mSiO2 and polyacrylic acid are mixed at a mass ratio of 1:2, and microcapsules are formed by spray drying; preferably, the silver loading of Ag@mSiO2 is 10 wt%, and the particle size of the microcapsules is 50-100 μm.
[0011] For the protective coating, the concentration of the silver nitrate solution is 0.1 M; the molecular weight of polyacrylic acid is 50,000-100,000, and the viscosity is 500-800 mPa·s; the parameters of the spray drying method are an inlet air temperature of 120 °C, an outlet air temperature of 60 °C, an atomization pressure of 0.3 MPa, and a feed rate of 10 mL / min.
[0012] For the protective coating, the pore diameter of the silver-loaded mesoporous silica in the intermediate layer is 8 ± 1 nm, the specific surface area is 800 m 2 / g, and the pore volume is 1.2 cm 3 / g.
[0013] The described protective coating, where the epoxy resin matrix is fluorosilicone resin with a silicon-oxygen bond content of ≥40% and remains stable below 500°C.
[0014] The preparation method of the above intelligent response type antibacterial-nano composite protective coating adopts gradient doping and ultraviolet curing processes, and includes the following steps:
[0015] (1) Disperse the ZnO@rGO composite in deionized water to form a ZnO@rGO dispersion; the concentration of the ZnO@rGO dispersion is 5wt%.
[0016] (2) Disperse the microcapsules in deionized water to form an Ag@mSiO2 / PAA suspension; the concentration of the Ag@mSiO2 / PAA suspension is 3wt%.
[0017] (3) Bottom layer coating: Mix fluorosilicone resin with TiO2 nanoparticles, and cure by ultraviolet light after coating; Intermediate layer coating: Spray the Ag@mSiO2 / PAA suspension and cure; Surface layer coating: Spray the ZnO@rGO dispersion and cure; Obtain the intelligent response type antibacterial-nano composite protective coating; Preferably, the doping amount of TiO2 nanoparticles is 1%-2% of the mass of fluorosilicone resin.
[0018] For the preparation method of the intelligent response type antibacterial-nano composite protective coating, in step (3), the curing parameters are: wavelength 365nm, light intensity 50mW / cm 2 , cure the surface layer for 6 - 10 minutes, cure the intermediate layer for 8 - 12 minutes, cure the bottom layer for 15 - 18 minutes, and avoid destroying the active ingredients of the microcapsules due to high temperature.
[0019] In the intelligent response type antibacterial-nano composite protective coating, the ZnO@rGO on the surface layer provides superhydrophobicity with a contact angle of ≥160°, the Ag@mSiO2 / PAA in the intermediate layer has slow-release antibacterial properties, and the bottom layer epoxy resin ensures adhesion with a grade of ≥4B. These three layers form an outer hydrophobic-inner tough structure.
[0020] Zn 2+ and Ag+ form a synergistic effect of biphasic nanoparticles through different antibacterial mechanisms. Zn 2+ destroys the bacterial cell membrane and inhibits metabolism, and Ag+ binds to the thiol groups on the cell membrane and inhibits the activity of intracellular enzymes. The combined use of the two can significantly improve the antibacterial effect and reduce bacterial drug resistance.
[0021] Beneficial effects: Compared with the prior art, the present invention has the following advantages:
[0022] (1) The silver-loaded mesoporous silica / polyacrylic acid microcapsules (Ag@mSiO2 / PAA) in the intermediate layer are pH-responsive materials and can dynamically respond to antibacterial. In an acidic environment (pH < 7), the microcapsules dissolve and release silver ions (Ag+ ), release amount ≥ 5 μg / cm 2 ·day. In an alkaline environment (pH > 7), the microcapsules self-close to inhibit the ineffective release of silver ions, and the release amount ≤ 1 μg / cm 2 ·day.
[0023] (2) The zinc oxide-graphene composite (ZnO@rGO) on the surface layer releases Zn 2+ , damaging the bacterial cell membrane. Silver ions (Ag + ) combine with the thiol groups in the bacterial cells to inhibit the activity of enzymes. When used in combination, they can have a two-phase synergistic antibacterial effect: the antibacterial rate ≥ 95%, and the drug resistance is reduced by 50%.
[0024] (3) The epoxy resin matrix at the bottom layer forms an outer hydrophobic (contact angle ≥ 160°)-inner tough structure through ultraviolet curing. The adhesion grade of the coating ≥ 4B, and it is resistant to scouring; the silicon-oxygen bond in the fluorosilicone resin matrix remains stable below 500 °C, and the hydrophobic angle ≥ 155°. Specific implementation manners
[0025] The following combines specific embodiments to further clarify the present invention. The embodiments are implemented on the premise of the technical solution of the present invention. It should be understood that these embodiments are only used to illustrate the present invention and not to limit the scope of the present invention.
[0026] Embodiment 1
[0027] Preparation of the intelligent response type antibacterial coating S1:
[0028] Step 1: Prepare Ag@mSiO2
[0029] Take mesoporous silica with a pore diameter of 8 ± 1 nm, a specific surface area of 800 m 2 / g, and a pore volume of 1.2 cm 3 / g, immerse it in a 0.1 M silver nitrate solution, and ultrasonically treat it for 1 hour; after drying, calcine it at 300 °C for 2 hours to obtain Ag@mSiO2 with a silver loading of 10 wt%.
[0030] Step 2: Prepare Ag@mSiO2 / PAA microcapsules
[0031] Mix Ag@mSiO2 and polyacrylic acid with a molecular weight of 100,000 in a mass ratio of 1:2, and add deionized water to prepare a suspension with a total solid content of 15 wt%;
[0032] Adopt spray drying method, with an inlet air temperature of 120 °C, an outlet air temperature of 60 °C, an atomization pressure of 0.3 MPa, and a feeding rate of 10 mL / min to obtain microcapsules with a particle size of 50 - 100 μm and an encapsulation rate of 92%.
[0033] Step 3: Preparation of ZnO@rGO composite
[0034] Disperse ZnO nanoparticles with an average particle size of 20 - 30 nm and rGO with a sheet size of 1 - 2 μm in ethanol at a mass ratio of 4:1, and ultrasonically treat for 2 hours; transfer to a high-pressure reactor, react at 160 °C for 8 hours, centrifuge, wash, and dry to obtain the ZnO@rGO composite.
[0035] Step 4: Gradient coating and ultraviolet curing
[0036] Bottom layer coating: Mix fluorosilicone resin with a silicon-oxygen bond content ≥ 40% and TiO2 nanoparticles, coat and then cure under ultraviolet light. Cure for 15 minutes at a wavelength of 365 nm and a light intensity of 50 mW / cm 2 under the condition; the doping amount of TiO2 nanoparticles is 1% of the mass of the fluorosilicone resin;
[0037] Intermediate layer coating: Spray a 3 wt% Ag@mSiO2 / PAA suspension and cure for 12 minutes at a wavelength of 365 nm and a light intensity of 50 mW / cm 2 under the condition;
[0038] Top layer coating: Spray a 5 wt% ZnO@rGO dispersion and cure for 10 minutes at a wavelength of 365 nm and a light intensity of 50 mW / cm 2 under the condition.
[0039] The thickness of the top layer of this protective coating is 80 μm, the thickness of the intermediate layer is 30 μm, and the thickness of the bottom layer is 120 μm.
[0040] Example 2
[0041] Preparation of intelligent response antibacterial coating S2:
[0042] Step 1: Preparation of Ag@mSiO2
[0043] Take mesoporous silica with a pore diameter of 8 ± 1 nm, a specific surface area of 800 m 2 / g, and a pore volume of 1.2 cm 3 / g, immerse it in a 0.1 M silver nitrate solution, and ultrasonically treat for 1 hour; after drying, calcine at 300 °C for 2 hours to obtain Ag@mSiO2 with a silver loading of 10 wt%.
[0044] Step 2: Preparation of Ag@mSiO2 / PAA microcapsules
[0045] Mix Ag@mSiO2 and polyacrylic acid with a molecular weight of 50,000 at a mass ratio of 1:2, and add deionized water to prepare a suspension with a total solid content of 15 wt%.
[0046] Using the spray drying method, with an inlet air temperature of 120 °C, an outlet air temperature of 60 °C, an atomization pressure of 0.3 MPa, and a feed rate of 10 mL / min, microcapsules with a particle size of 50 - 100 μm and an encapsulation efficiency of 92% were obtained.
[0047] Step 3: Prepare ZnO@rGO composite
[0048] Disperse ZnO nanoparticles with an average particle size of 20 - 30 nm and rGO with a sheet size of 1 - 2 μm in ethanol at a mass ratio of 4:1, and ultrasonically treat for 2 hours; transfer to a high-pressure reactor, react at 160 °C for 8 hours, centrifuge, wash, and dry to obtain the ZnO@rGO composite.
[0049] Step 4: Gradient coating and ultraviolet curing
[0050] Bottom layer coating: Mix a fluorosilicon resin with a silicon-oxygen bond content of ≥40% and TiO2 nanoparticles, coat and then cure under ultraviolet light; cure for 18 minutes under the conditions of a wavelength of 365 nm and a light intensity of 50 mW / cm 2 The doping amount of TiO2 nanoparticles is 2% of the mass of the fluorosilicon resin;
[0051] Intermediate layer coating: Spray a 3 wt% Ag@mSiO2 / PAA suspension and cure for 8 minutes under the conditions of a wavelength of 365 nm and a light intensity of 50 mW / cm 2 conditions;
[0052] Top layer coating: Spray a 5 wt% ZnO@rGO dispersion and cure for 6 minutes under the conditions of a wavelength of 365 nm and a light intensity of 50 mW / cm 2 conditions.
[0053] The thickness of the top layer of this protective coating is 50 μm, the thickness of the intermediate layer is 40 μm, and the thickness of the bottom layer is 150 μm.
[0054] Example 3
[0055] Preparation of the intelligent response antibacterial coating S3:
[0056] Step 1: Prepare Ag@mSiO2
[0057] Take mesoporous silica with a pore diameter of 8 ± 1 nm, a specific surface area of 800 m 2 / g, and a pore volume of 1.2 cm 3 / g, immerse it in a 0.1 M silver nitrate solution, and ultrasonically treat for 1 hour.
[0058] After drying, calcine at 300 °C for 2 hours to obtain Ag@mSiO2 with a silver loading of 10 wt%.
[0059] Step 2: Prepare Ag@mSiO2 / PAA microcapsules
[0060] Mix Ag@mSiO2 with polyacrylic acid with a molecular weight of 100,000 at a mass ratio of 1:2, and add deionized water to prepare a suspension with a total solid content of 15 wt%.
[0061] Using the spray drying method, with an inlet air temperature of 120 °C, an outlet air temperature of 60 °C, an atomization pressure of 0.3 MPa, and a feeding rate of 10 mL / min, microcapsules with a particle size of 50 - 100 μm are obtained, and the encapsulation efficiency is 92%.
[0062] Step 3: Prepare ZnO@rGO composite
[0063] Disperse ZnO nanoparticles with an average particle size of 20 - 30 nm and reduced graphene oxide with a sheet size of 1 - 2 μm in ethanol at a mass ratio of 4:1, and ultrasonically treat for 2 hours.
[0064] Transfer to a high-pressure reaction kettle, react at 160 °C for 8 hours, centrifuge, wash, and dry to obtain the ZnO@rGO composite.
[0065] Step 4: Gradient coating and ultraviolet curing
[0066] Bottom layer coating: Mix fluorosilicone resin with a silicon-oxygen bond content ≥ 40% and TiO2 nanoparticles, coat and then cure under ultraviolet light. The doping amount of TiO2 nanoparticles is 1% of the mass of the fluorosilicone resin; cure for 15 minutes under the conditions of a wavelength of 365 nm and a light intensity of 50 mW / cm 2 2.
[0067] Intermediate layer coating: Spray a 3 wt% Ag@mSiO2 / PAA suspension, and cure for 12 minutes under the conditions of a wavelength of 365 nm and a light intensity of 50 mW / cm 2 2.
[0068] Top layer coating: Spray a 5 wt% ZnO@rGO dispersion, and cure for 10 minutes under the conditions of a wavelength of 365 nm and a light intensity of 50 mW / cm 2 2.
[0069] The thickness of the top layer of this protective coating is 100 μm, the thickness of the intermediate layer is 50 μm, and the thickness of the bottom layer is 100 μm.
[0070] Test the antibacterial rate of the prepared intelligent response antibacterial coating according to GB / T 21866-2008 "Determination Method and Antibacterial Effect of Antibacterial Coatings (Paint Films)", measure the silver ion release amount using an inductively coupled plasma mass spectrometer, test the adhesion according to ASTM D3359-23 "Standard Test Method for Evaluating Adhesion by Tape Test", and test the hydrophobicity according to ASTM D7334-08 "Standard Practice for Measuring the Surface Wettability of Coatings, Pigments, and Substrates by the Advancing Contact Angle Method". The results are shown in Table 1.
[0071] Performance test results of the protective coatings prepared in Examples 1-3 in Table 1
[0072]
[0073] The above are only the preferred embodiments of the present invention. It should be noted that for those of ordinary skill in the art, without departing from the principle of the present invention, several improvements and refinements can be made, and these improvements and refinements should also be regarded as the protection scope of the present invention.
Claims
1. An intelligent responsive antibacterial-nano composite protective coating, characterized in that, It consists of the following three layers: (a) Surface layer: zinc oxide-graphene composite; (b) Intermediate layer: silver-loaded mesoporous silica / polyacrylic acid microcapsules; (c) Bottom layer: epoxy resin matrix.
2. The protective coating according to claim 1, characterized in that The thickness of the surface layer is 50-100 μm, the thickness of the intermediate layer is 30-50 μm, and the thickness of the bottom layer is 100-150 μm.
3. The protective coating according to claim 1, wherein Disperse rGO and ZnO nanoparticles in ethanol, perform ultrasonic treatment, transfer to a high-pressure reactor, react at 160 °C for 8 hours, centrifuge and wash, and dry to obtain the ZnO@rGO composite.
4. The protective coating according to claim 1, wherein In the zinc oxide-graphene composite, the mass ratio of ZnO nanoparticles to rGO is 4:1, the average particle size of ZnO nanoparticles is 20-30 nm, and the sheet size of rGO is 1-2 μm.
5. The protective coating according to claim 1, wherein Immerse mesoporous silica in a silver nitrate solution, perform ultrasonic treatment, and then calcine at 300 °C for 2 hours to obtain Ag@mSiO2; then mix Ag@mSiO2 and polyacrylic acid in a mass ratio of 1:2 and form microcapsules by spray drying.
6. The protective coating according to claim 5, wherein The concentration of the silver nitrate solution is 0.1 M; the molecular weight of polyacrylic acid is 50,000-100,000, and the viscosity is 500-800 mPa·s; the parameters of the spray drying method are an inlet air temperature of 120 °C, an outlet air temperature of 60 °C, an atomization pressure of 0.3 MPa, and a feed rate of 10 mL / min.
7. The protective coating according to claim 1, wherein The silver-loaded mesoporous silica of the intermediate layer has a pore diameter of 8 ± 1 nm, a specific surface area of 800 m 2 / g, and a pore volume of 1.2 cm 3 / g.
8. The protective coating according to claim 1, characterized in that, The epoxy resin matrix is a fluorosilicone resin with a silicon-oxygen bond content ≥ 40%.
9. The preparation method of the intelligent response type antibacterial-nano composite protective coating according to any one of claims 1-8, characterized in that, It includes the following steps: (1) Disperse the ZnO@rGO composite in deionized water to form a ZnO@rGO dispersion; the concentration of the ZnO@rGO dispersion is 5 wt%. (2) Disperse the microcapsules in deionized water to form an Ag@mSiO2 / PAA suspension; the concentration of the Ag@mSiO2 / PAA suspension is 3 wt%. (3) Bottom layer coating: Mix the fluorosilicone resin and TiO2 nanoparticles, and perform ultraviolet curing after coating. Intermediate layer coating: Spray the Ag@mSiO2 / PAA suspension and cure. Surface layer coating: Spray the ZnO@rGO dispersion and cure. Obtain an intelligent response antibacterial-nano composite protective coating.
10. The preparation method of the intelligent response type antibacterial-nano composite protective coating according to claim 9, characterized in that, Step (3), the curing parameters are: wavelength 365 nm, light intensity 50 mW / cm 2 , the surface layer is cured for 6 - 10 minutes, the middle layer is cured for 8 - 12 minutes, and the bottom layer is cured for 15 - 18 minutes.
Citation Information
Patent Citations
A superhydrophobic, corrosion-resistant, and antibacterial nano-coating, coating and its preparation method
CN114561138B
Preparation method of super-hydrophobic self-cleaning nano coating
CN119081540A
Graphene nano coating and preparation method thereof
CN119192972A